Facile preparation of polymer coating on reduced graphene oxide sheets by plasma polymerization - Yi Yang (Taylor & Francis Group, 2019)
Surface modification was needed in the application of nanoparticles. In this work, a simple method was proposed to prepare polymer coatings on reduced graphene oxide (rGO) sheets. A polymer coating of plasma polymethyl methacrylate (pPMMA) was synthesized on the surface of rGO by plasma polymerization using dielectric barrier discharge plasma equipment. There was good adhesion between the pPMMA coating and the surface of rGO. Furthermore, the pPMMA coating consisted of two layers classified by their interactions with rGO:pPMMA in the outer layer physically adhered to the surface and pPMMA of the under layer interacted with rGO by chemical bonding. The thicknesses of the outer and under layers were 1.5–3 nm and 2–3.5 nm, respectively. Moreover, the morphology and thickness of pPMMA coatings could be effectively regulated by controlling the input voltage and processing time. The process of the deposition of pPMMA coating was preliminarily studied and discussed in this work. We believed that this strategy could open up an avenue for the surface modification of other kinds of nanoparticles.